Immunogenicity of influenza H1N1 vaccination in mixed connective tissue disease: effect of disease and therapy (Clinics, 2013)
OBJECTIVE: To assess the potential acute effects regarding the immunogenicity and safety of non-adjuvanted influenza A H1N1/2009 vaccine in patients with mixed connective tissue disease and healthy controls. METHODS: Sixty-nine mixed connective tissue disease patients that were confirmed by Kasukawa's classification criteria and 69 age- and gender-matched controls participated in the study; the participants were vaccinated with the non-adjuvanted influenza A/California/7/2009 (H1N1) virus-like strain. The percentages of seroprotec-tion, seroconversion, geometric mean titer and factor increase in the geometric mean titer were calculated. The patients were clinically evaluated, and blood samples were collected pre- and 21 days post-vaccination to evaluate C-reactive protein, muscle enzymes and autoantibodies. Anti-H1N1 titers were determined using an influenza hemagglutination inhibition assay. ClinicalTrials.gov: NCT01151644. RESULTS: Before vaccination, no difference was observed regarding the seroprotection rates (p = 1.0) and geometric mean titer (p = 0.83) between the patients and controls. After vaccination, seroprotection (75.4% vs. 71%, (p = 0.7), seroconversion (68.1% vs. 65.2%, (p = 1.00) and factor increase in the geometric mean titer (10.0 vs. 8.0, p = 0.40) were similar in the two groups. Further evaluation of seroconversion in patients with and without current or previous history of muscle disease (p = 0.20), skin ulcers (p = 0.48), lupus-like cutaneous disease (p = 0.74), secondary Sjogren syndrome (p = 0.78), scleroderma-pattern in the nailfold capillaroscopy (p = 1.0), lymphopenia #1000/mm³ on two or more occasions (p = 1.0), hypergammaglobulinemia $1.6 g/d (p = 0.60), pulmonary hypertension (p = 1.0) and pulmonary fibrosis (p = 0.80) revealed comparable rates. Seroconversion rates were also similar in patients with and without immunosuppressants. Disease parameters, such as C-reactive protein (p = 0.94), aldolase (p = 0.73), creatine phosphokinase (p = 0.40) and ribonucleoprotein antibody levels (p = 0.98), remained largely unchanged pre and post-vaccination. No severe side effects were reported. CONCLUSIONS: The non-adjuvanted influenza A/H1N1 vaccination immune response in mixed connective tissue disease patients is adequate and does not depend on the disease manifestations and therapy.